Family Planning in Substance Use Disorder Treatment Centers: Opportunities and Challenges. (18th September 2016) - Robinowitz, Natanya; Muqueeth, Sadiya; Scheibler, Jill; Salisbury-Afshar, Elizabeth; Terplan, Mishka
ABSTRACT: Background : Alcohol, tobacco, and drug use during pregnancy can cause a range of adverse birth outcomes. Promoting family planning among women with substance use disorders (SUD) can help reduce substance exposed pregnancies. Objectives : We conducted qualitative research to determine the acceptability and feasibility of offering family planning education and services SUD treatment centers. Methods : Focus groups and in-depth interviews were conducted with clients, staff and medical providers at three treatment centers. Interviews were transcribed and data was analyzed using a flexible coding scheme. Results : Clients reported being interested in family planning services while they were in treatment. Most preferred to receive these services onsite. Providers also felt that services should be received onsite, though cited several barriers to implementation, including time constraints and staff levels of comfort with the subject. Conclusions/Importance : Women in SUD treatment are open to the integration of family planning services into treatment. Treatment centers have the opportunity to serve as models of client-centered health homes that offer a variety of educational, preventive, and medical services for women in both treatment and recovery.